MIXTURE OF CHARCOAL KAYU GALAM (Melaleuca leucadendron LINN ) AND SHELL CANDLENUT (Aleurites moluceana WILD) - LUSYIANI LUSYIANI (Lambung Mangkurat University-Indonesia, 2011)
ABSTRACT. The purpose of this study was to determine the effect of mixture composition Galam wood with walnut shells to the quality of the resulting charcoal briquettes. The results and analysis of variance showed that the treatment given very real effect on the moisture content, ash content, the levels of substances fly, carbon residue, and the calorific value and significantly affect the density. The addition of hazelnut shell causes an increase in moisture content, ash content, and levels of substances that reduce the amount of carbon fly and the rest of the calorific value generated. The addition of hazelnut shells up to 50% (treatment A3) results in a briquette charcoal briquettes are still compliant imports (Japanese standard). Based on the results of the test, the charcoal briquettes produced have physical and chemical properties as follows: the average water content of 7.949%, the average ash content of 2.855%, the average levels of substance flew 29.510%, the average carbon remaining 67.652%, average the average density of 0.779 gram/cm3, and the average calorific value of 6202.6594 cal / gram.Keywords: moisture content, ash content, carbon residue, ABSTRAK. Tujuan penelitian ini adalah untuk mengetahui pengaruh komposisi campuran kayu galam dengan tempurung kemiri terhadap kualitas briket arang yang dihasilkan. Hasil penelitian dan analisis sidik ragam menunjukkan bahwa perlakuan yang diberikan berpengaruh sangat nyata terhadap kadar air, kadar abu, kadar zat terbang, karbon sisa, dan nilai kalor serta berpengaruh nyata terhadap kerapatan. Penambahan tempurung kemiri menyebabkan kenaikan kadar air, kadar abu, dan kadar zat terbang sehingga mengurangi jumlah karbon sisa dan nilai kalor yang dihasilkan. Penambahan tempurung kemiri sampai 50% (perlakuan A3) menghasilkan briket arang yang masih memenuhi standar briket impor (standar Jepang).Berdasarkan hasil pengujian, briket arang yang dihasilkan mempunyai sifat fisik dan kimia sebagai berikut : rata-rata kadar air 7,949%, rata-rata kadarabu 2,855%, rata-rata kadar zat terbang 29,510%, rata-rata karbon sisa 67,652%, rata-rata kerapatan 0,779 gram/cm3, dan rata-rata nilai kalor 6202,6594 cal/gram.Kata Kunci : kadar air, kadar abu, karbon sisa